Recent Advances in the Development of Non-PIKKs Targeting Small Molecule Inhibitors of DNA Double-Strand Break Repair - Kelm, Jeremy M.; Samarbakhsh, Amirreza; Pillai, Athira; VanderVere-Carozza, Pamela S.; Aruri, Hariprasad; Pandey, Deepti S.; Pawelczak, Katherine S.; Turchi, John J.; Gavande, Navnath S. (Frontiers in Oncology, 2022)
The vast majority of cancer patients receive DNA-damaging drugs or ionizing radiation (IR), yet the efficacy of these therapies is tempered by DNA repair and DNA damage response (DDR) pathways. Aberrations of DNA repair and the DDR are observed in every cancer subtype which promote de novo carcinogenesis, genomic instability, and ensuing resistance to current cancer therapy. Additionally, stalled or collapsed DNA replication forks present a catastrophic challenge to the double-strand DNA break (DSB) repair system. Of the various inducible DNA lesions, DSBs are the most lethal and thus desirable in the setting of cancer treatment. In mammalian cells, DSBs are typically repaired by the non-homologous end joining pathway (NHEJ) or the high-fidelity homology directed repair (HDR) pathway. Targeting DSB repair pathways using small molecular inhibitors offers a promising mechanism to synergize DNA-damaging drugs and IR while selective inhibition of the NHEJ pathway can induce synthetic lethality in HDR-deficient cancer subtypes. Selective inhibitors of the NHEJ pathway and alternative DSB-repair pathways may also see future use in precision genome editing to direct repair of the DSBs created by the HDR pathway. In this review, we highlight the recent advances in the development of inhibitors of the non-phosphatidylinositol 3-kinase-related kinases (non-PIKKs) members of the NHEJ, HDR and minor backup SSA and alt-NHEJ DSB-repair pathways. The targeted inhibitors described within the non-PIKKs DSB repair mediators including Ku70/80, Artemis, DNA Ligase IV, XRCC4, MRN complex, RPA, RAD51, RAD52, ERCC1-XPF, and DNA polymerase θ. While the DDR PIKKs remain intensely pursued as therapeutic targets, small molecule inhibition of non-PIKKs represents an emerging opportunity in drug discovery that offers considerable potential to impact cancer treatment.